Edukasi dan Pemberdayaan kepada Ibu Hamil dan Ibu Balita dalam Upaya Pencegahan Stunting pada Balita di Desa Slateng, Ledokombo dan Desa Jatian Pakusari - Asa Falahi; Dewi Rashati; Hadi Barru Hakam Fajar Siddiq (Dental Agromedis, 2024)
Stunting is a nutritional problem caused by a long-term lack of nutritional intake during the first 1000 days of life (HPK) which is a critical period, resulting in impaired growth in children, namely the child's height is lower or shorter (dwarf) than the standard age. Currently, the stunting rate in the Jember Regency is recorded at 37.08 percent. Ledokombo and Pakusari sub-districts are villages with high stunting rates in Jember City. Particularly in Slateng Ledokombo Village, which has the five highest incidences of stunting in Jember. The activity aims to increase the nutritional knowledge and behavior of pregnant women and mothers under five to prevent stunting. Educational activities with stunting prevention were carried out for respondents consisting of pregnant women and mothers with toddlers. This activity was carried out by delivering material using previously designed leaflets as a health promotion tool. The distributed leaflet was entitled “Prevent Stunting with Vitamin & Mineral Intake, Clean and Healthy Behavior During the First 1000 Days of Life”. Based on the activities' results, the two villages (Jatian and Slateng) were included in the good category, before and after being given education by the executors of the Jember Pharmacy Academy. The community already knows about stunting and its prevention. This cannot be separated from the role of the government through Cadres and Village Midwives in providing provision, information, and education to the community. Community Service activities carried out by the Jember Pharmacy Academy community increase public knowledge about stunting and its prevention. This can be seen in the results of the post-test questionnaire filled out by activity participants.Keywords: Stunting, Education, Empowerment.